If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 236 = 0 + n Remove the zero: 236 = n Solving 236 = n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 236 + -1n = n + -1n Combine like terms: n + -1n = 0 236 + -1n = 0 Add '-236' to each side of the equation. 236 + -236 + -1n = 0 + -236 Combine like terms: 236 + -236 = 0 0 + -1n = 0 + -236 -1n = 0 + -236 Combine like terms: 0 + -236 = -236 -1n = -236 Divide each side by '-1'. n = 236 Simplifying n = 236
| c^2=12 | | 8.6t+3.34=-51.70 | | b^2=18 | | 4w=68 | | .6y-6=2 | | x*ln(3)=2-x*ln(2) | | 0.02x-1.56=0.8x | | x-34=72 | | 14=.6(9y-15) | | 10c=260 | | 3(2a-6)=34 | | 9h=207 | | 34(19-5.5x)=16(5x-8)+53.1 | | 7g=91 | | 32=.5x(x+12) | | 7p=56 | | -1+-10= | | -3.45-1.5c=6.1(c+2.3) | | 0.3a-1.2=0.5a | | 36=.5x(x-5) | | f+20=61 | | 14a-10=19(a-3) | | 2.8x+65=5.3x+10 | | 8x+5y = 6 | | 3n-8=37+8n | | 7x-7=3x+9 | | e+49=61 | | 26-2(5+6)= | | x-6+2=4 | | 1.7m+7.28=-9.04 | | 8z-5=-11+5z | | d+13=35 |